If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(y-7)=(5-8y)-12
We move all terms to the left:
3(y-7)-((5-8y)-12)=0
We add all the numbers together, and all the variables
3(y-7)-((-8y+5)-12)=0
We multiply parentheses
3y-((-8y+5)-12)-21=0
We calculate terms in parentheses: -((-8y+5)-12), so:We get rid of parentheses
(-8y+5)-12
We get rid of parentheses
-8y+5-12
We add all the numbers together, and all the variables
-8y-7
Back to the equation:
-(-8y-7)
3y+8y+7-21=0
We add all the numbers together, and all the variables
11y-14=0
We move all terms containing y to the left, all other terms to the right
11y=14
y=14/11
y=1+3/11
| 6x+108=246 | | 6b+2=4b | | y-1.82=8.72 | | x3+2005x+2006=0 | | 2a-10=3a | | x+77=117 | | 6p-8p=4(6+p)+3(7p+1) | | x^2-2x-0.91=0 | | 32=2x+2(3x-4) | | x^2+2x-0.91=0 | | −7x2+5=10 | | 6x(5x-2)+12=30 | | 9y-24=3y | | 2x+24+x+18=14+11 | | 7x|10=6 | | 10+2+x+5=5x-3 | | 7x*10=6 | | x2-4x+16=0 | | -5(n+1)=-6(4+4n | | 14-4z=2(17-5) | | 3y+270=0 | | 24+x+2x+29=17 | | x2+6x+12=0 | | -19=36+5x | | -6=-2x=18 | | 153=43-11x | | 4x^+4x-5=-30 | | 12x+7=10x+25 | | 8x-5=3-16x | | 5y^2+4y+28=0 | | 6(x-1)+1=-35 | | 13.75+x=20.80 |